Taṭwīr al-Kitāb al-Madrasī “Buku Pembelajaran Bahasa Arab Kelas V Kurikulum 2013” Bi al-Wasā’il as-Sam`iyyah al-Baṣariyyah `Alā Fahm al-Qawa`id an-Naḥwiyyah Bi al-Madrasah al-Ibtidāiyyah al-Islāmiyyah al-Ahliyyah Cendekia Darussalam - Rauzatun Nufus; Buhori Muslim (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Textbooks are the main media used by teachers and students in instructional process. Therefore, the qawaid nahwu learning book that are unstructured, general and not equipped with various examples, it will make students feel bored and do not understand about the qawaid nahwu. In this study, the researcher was developing an Arabic learning book for grade five in 2013 curriculum by using audio-visual media. This research was designed to find out how to develop Arabic learning books for grade five in 2013 curriculum using audio-visual media and how to determine the effectiveness of Arabic learning books for grade five in 2013 curriculum by using audio-visual media. Furthermore, the Research and Development model by Borg and Gall was conducted in this study as research method. Data collection consisted of interviews, questionnaires and tests. In addition, the participants in this study were 280 students as population, and the students in all grade five insists of 25 students were taken as sample. according to the results, the researcher found that book development has been carried out through 10 stages: Potential and problems, gathering information, product design, design validation in this the value of the first expert was 78 % and the second expert was 77 % it showed that this bool agrees to be used learning qawaid nahwiyah, design improvement, product testing, product revision, usage testing, product revision and mass product manufacturing . meanwhile, the results of the effectiveness test using the t test showed that the t count was greater than the t table, namely 4.1 based on a significance level of 5% 2.06 and 1% 2.80.